Two-coordinate electromagnetic sensor - V. A. Zakharenko; A. G. Shakhova; A. G. Shkayev (Омский научный вестник)
A two-coordinate non-contact sensor for detecting increased sensitivity is developed, which operates on the principle of electromagnetic saturation of the transformer core under the action of an external magnetic field. The sensor operation, its design version is described, functional and electrical circuits are shown. The results of implementation of prototype sensors in the process of production of technical carbon for control of rotation of drying drums are presented. The sensors retain detection capability when removing the object of control caused by thermal expansion of the material of the drum structure by 150-200 mm.